Stopping Investigation and Prosecution to Realize Restorative Justice - Konoras, Isyana Kurniasari (Kawanua International Journal of Multicultural Studies, 2023)
This study aims to analyze the effectiveness of penal mediation efforts in achieving restorative justice and to analyze penal mediation efforts in stopping the investigation and prosecution of criminal cases. The type of research used is normative legal research, relying on and using library data, namely secondary data in the field of law. The technique of obtaining legal materials is by means of library research by collecting legal materials by reading, quoting, recording and understanding various legal literature and laws. The results of the study show that 1) the function and role of the state through penal mediation will reduce the burden on the state in punishing and imprisoning criminals because amicable and compromise solutions can be reached for the creation of restorative justice. 2) Termination of Prosecution because there has been a settlement of cases outside the court as stipulated in PERJA No. 15 of 2020 Article 3 paragraph (2) is the scope of settlement of criminal cases by mediation as an effort to realize restorative justice which is pursued with material and formal requirements.